PROFIL SIKAP DAN KEIASAAN BELAJAR SISWA DITINJAU DARI TINGKAT PENDIDIKN IBU KELAS VII SMP NEGERI 14 PEKANBARU - Andriyani, Tuti; Rosmawati, Rosmawati; Yakub, Elni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims 1) To know the description of students' attitude and study habits in the mastery of teaching materials based on the level of education of the mother 2) To know the description of student's attitude and study habits in learning skill based on mother's education level 3) To know the description of attitude and habit Learning students in using learning tools based on the level of education of the mother 4) To know the description of student attitudes and habits in understanding the personal condition based on the level of education of the mother 5) To know and understand the attitudes and habits of learning students in understanding the learning environment and socio-emotional Based on maternal education level. The subjects of the study were the students of class VII. The sample determination uses a total sample which means the whole population becomes the sample. The research method used is qualitative method with descriptive approach that is qualitative method as a process of inquiry to comprehend social problem or human problem, based on the creation of holistic picture in the form of words. The results showed almost all students have the attitude and habits of learning is not good.Key Words: Attitude, Study Habits, Education Level Of Mother